Ocular manifestations in acute herpes zoster ophthalmicus - Ranida Thamphithak (2020)
© 2019, Siriraj Medical Journal. Objective: To determine the prevalence and clinical predictors of ocular involvement in acute herpes zoster ophthalmicus. Methods: A retrospective chart review of 167 patients presenting with acute herpes zoster ophthalmicus at the Outpatient Department of Ophthalmology, Siriraj Hospital, was performed. All skin lesions along the ophthalmic branch of the trigeminal nerve (CN V1) and ocular inflammatory signs were observed and documented. Results: A total of 160 cases were analyzed. The prevalence of ocular inflammation in acute herpes zoster ophthalmicus was 73.1% (117/160). The types of ocular inflammations included conjunctival injection (99.1%), keratitis (51.3%), and iridocyclitis (21.4%). Nasociliary skin lesions (Hutchinson's sign) were the best predictor of ocular inflammation in acute herpes zoster ophthalmicus (p = 0.006, OR = 3.6, 95% CI: 1.5-9.1). Other factors associated with ocular inflammation were a period of longer than 4 days from the onset of rash to an eye examination (p = 0.007, OR = 3.2, 95% CI: 1.4-7.5), and the initiation of systemic acyclovir treatment after 3 days from rash onset (p = 0.037, OR = 2.3, 95% CI: 1.05-4.96). Conclusion: There is a high prevalence of ocular inflammation in acute herpes zoster ophthalmicus, especially among individuals with Hutchinson's sign and delayed systemic acyclovir treatment. General practitioners should be aware of ocular involvement and refer high-risk patients for a complete ophthalmologic assessment.